Inflation inequality in the United States - Bart Hobijn; David Lagakos (Federal Reserve Bank of New York, 2003)
Inflation is often assumed to affect all people in the same way. In practice, differences in spending patterns across households and differences in price increases across goods and services lead to unequal levels of inflation for different households. In this paper, we measure the degree of inequality in inflation across U.S. households for the period 1987-2001. Our results suggest that the inflation experiences of U.S. households vary significantly. Most of the differences can be traced to changes in the relative prices of education, health care, and gasoline. We find that cost of living increases are generally higher for the elderly, in large part because of their health care expenditures, and that the cost of living for poor households is most sensitive to (the historically large) fluctuations in gasoline prices. To our surprise, we also find that those households that experience high inflation in one year do not generally face high inflation in the next year. That is, we do not find much household-specific persistence in inflation disparities.
Keywords: C43; D12; D39; 330; consumption price inflation; inequality; household inflation rates; Inflation; Privater Haushalt; Inflationsrate; USA